Renal Function in De Novo Liver Transplant Recipients Receiving Different Prolonged‐Release Tacrolimus Regimens—The DIAMOND Study. Issue 7 (23rd February 2015) - TruneČka, P.; Klempnauer, J.; Bechstein, W. O.; Pirenne, J.; Friman, S.; Zhao, A.; Isoniemi, H.; Rostaing, L.; Settmacher, U.; Mönch, C.; Brown, M.; Undre, N.; et al.
<x xml:space="preserve">Abstract</x> DIAMOND: multicenter, 24‐week, randomized trial investigating the effect of different once‐daily, prolonged‐release tacrolimus dosing regimens on renal function after de novo liver transplantation. Arm 1: prolonged‐release tacrolimus (initial dose 0.2mg/kg/day); Arm 2: prolonged‐release tacrolimus (0.15–0.175mg/kg/day) plus basiliximab; Arm 3: prolonged‐release tacrolimus (0.2mg/kg/day delayed until Day 5) plus basiliximab. All patients received MMF plus a bolus of corticosteroid (no maintenance steroids). Primary endpoint: eGFR (MDRD4) at Week 24. Secondary endpoints: composite efficacy failure, BCAR and AEs. Baseline characteristics were comparable. Tacrolimus trough levels were readily achieved posttransplant; initially lower in Arm 2 versus 1 with delayed initiation in Arm 3. eGFR (MDRD4) was higher in Arms 2 and 3 versus 1 (p = 0.001, p = 0.047). Kaplan–Meier estimates of composite efficacy failure‐free survival were 72.0%, 77.6%, 73.9% in Arms 1–3. BCAR incidence was significantly lower in Arm 2 versus 1 and 3 (p = 0.016, p = 0.039). AEs were comparable. Prolonged‐release tacrolimus (0.15–0.175mg/kg/day) immediately posttransplant plus basiliximab and MMF (without maintenance corticosteroids) was associated with lower tacrolimus exposure, and significantly reduced renal function impairment and BCAR incidence versus prolonged‐release tacrolimus (0.2mg/kg/day) administered immediately posttransplant. Delayed higher‐dose prolonged‐release tacrolimus initiation significantly reduced renal function impairment compared with immediate posttransplant administration, but BCAR incidence was comparable.